2005
DOI: 10.1007/s10620-005-2763-x
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Helicobacter pylori–Induced Cytotoxicity by Red Ginseng

Abstract: Helicobacter pylori has been known to provoke gastric inflammation, ulceration, and DNA damage, based on which WHO defined H. pylori as a class I carcinogen. Although ginseng, the root of Panax ginseng C.A. Meyer, has been reported to possess antiadhesion or antimicrobial activity against H. pylori, in this study, we examined the protective effect of red ginseng extracts (RGE) against H. pylori-induced cytotoxicity and DNA damage. RGE significantly attenuated both H. pyloriinduced DNA damage assessed by comet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Apparent hindrance of DNA binding of redoxsensitive transcription factor, NF-κB, which was triggered by H pylori infection, was seen after RGE treatment in dosedependent manner. Because RGE pretreatment significantly reduced proinflammatory cytokine, IL-8, and protected gastric epithelium against H pylori-induced cytotoxicity in our previous study [20], we repeatedly examined whether RGE treatment can decrease the IL-8 transcripts after H pylori infection (see Fig. 4B).…”
Section: Suppression Of Endogenous 5-lox Expression Through the Inactmentioning
confidence: 97%
See 2 more Smart Citations
“…Apparent hindrance of DNA binding of redoxsensitive transcription factor, NF-κB, which was triggered by H pylori infection, was seen after RGE treatment in dosedependent manner. Because RGE pretreatment significantly reduced proinflammatory cytokine, IL-8, and protected gastric epithelium against H pylori-induced cytotoxicity in our previous study [20], we repeatedly examined whether RGE treatment can decrease the IL-8 transcripts after H pylori infection (see Fig. 4B).…”
Section: Suppression Of Endogenous 5-lox Expression Through the Inactmentioning
confidence: 97%
“…Based on our previous report that the rescuing action of red ginseng extract (RGE) from H pylori-associated cytotoxicity through the efficient inhibitory actions of both MAPK and repression of redox-sensitive transcription factor [20] and on other's reports showing the influence of ginsenoside isolate or panaxynol isolated from ginseng on either intracellular calcium [21,22] or mediators like COX-2 and nuclear factor (NF)-κB [23,24], we hypothesized that RGE can modulate H pylori-associated gastric inflammation through modulating LOX activities and measured the LOX activities by both reverse phase-high performance liquid chromatography (RP-HPLC) and thin layer chromatography (TLC) and checked its expression by Western blotting in gastric mucosal cells.…”
Section: Abstract Helicobacter Pylori Red Ginseng 5(s)-hete 5-lmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the antioxidant, antibacterial, and anti-inflammatory effects of ginseng [27][28][29][30][31][32]. Ginsenoside Rb1 was shown to inhibit lipopolysaccharide-induced expression of the proinflammatory cytokine tumor necrosis factor (TNF)-a, while acidic polysaccharide from ginseng reportedly inhibits the adherence of H. pylori to human gastric epithelial cells (Fig.…”
Section: Korean Red Ginseng In the Mitigation Of H Pyloriassociated mentioning
confidence: 99%
“…Therefore, can ginseng be used to treat H. pylori-infected gastric mucosal cells? Our group has documented that Korean red ginseng alleviates H. pylori-induced cytotoxicity [27] and mitigates oxidative stress-induced DNA mutation. In addition, Korean red ginseng decreased H. pylori-stimulated interleukin (IL)-8 expressions, supporting its use as a medicinal phytonutrient in H. pylori infection [21].…”
Section: Korean Red Ginseng In the Mitigation Of H Pyloriassociated mentioning
confidence: 99%